Pengawasan Pada Wilayah Perbatasan Laut Suatu Negara - Imbiri, Rival Jou; Peilouw, Johanis Steny Franco; Leatemia, Wilshen (Faculty of Law Universitas Pattimura, 2024)
Indonesia is an archipelagic country with many natural resources. With the ratification of UNCLOS 1982, Indonesia's maritime territory became wider. This opens up opportunities for legal violations due to lack of supervision in border areas, such as the entry of Rohingya refugee ships into Indonesian territory. Apart from the influx of Rohingya into Indonesian waters, various kinds of legal violations also occur in Indonesian waters, one of which is the case of illegal fishing which is very detrimental to the Indonesian state. This type of research is normative juridical where research is carried out by collecting primary, secondary and tertiary data. obtained using literature study. The results of this research show that supervision of Indonesia's maritime border areas has been carried out in accordance with the provisions stipulated in the 1982 Convention on the Law of the Sea. By ratifying UNCLOS 1982, Indonesia has issued and established national legislation relating to supervision and law enforcement at sea. . Apart from that, Indonesia also has various ministries/institutions that have the authority to carry out supervisory and law enforcement functions in Indonesian maritime areas. Legal problems faced by Indonesia in carrying out supervision in maritime border areas include overlapping roles, duties and functions (authorities) and regulations, weak coordination between agencies that have authority at sea, the absence of special institutions that have dimensional functions including supervision and law enforcement. , and limited facilities and infrastructure used to monitor and enforce laws in maritime areas.